(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The increasing demand for renewable energy systems has accelerated the development of different marine energy technologies. Among them, the Wave and Tidal Energy (WTE) systems represent a promising solution. However, the successful long-term stability and operation of WTE devices rely critically on robust foundations capable of withstanding the complex and dynamic marine environment, including static and cyclic loads, currents and tides as well as potential scour and erosion during the life cycle of the structure. Defining the suitable location and designing an effective foundation system require a reliable ground model with accurate geotechnical properties. For this purpose, an integrated approach to soil and rock characterization, combining geophysical surveys, in situ testing, sampling techniques and laboratory analyses is a suitable methodology for obtaining robust and representative ground models. Marine geophysical surveys are indirect methods that provide high-quality data of seabed morphology and sub-surface stratigraphy, identifying potential hazards such as buried obstacles, existing pipelines or cables, bedrock variations, geological faults, etc. to optimally select suitable locations for WTE systems. This information also guides the location for more detailed investigations including in-situ tests such as CPTU or T-bar for very soft soils, and sampling. There is a wide range of tools designed to get information of the seabed in case of soil, such as vibrocorer or pistoncorer that allow recovering samples up to 12m length depending on soil conditions and expected sample quality. In case of rocky seabed, the options are limited, and the use of remotely operated submersible drilling rigs may be a suitable alternative to the use of jack-up or drilling vessels. Recovered samples are finally analysed in the laboratory for a full integration of data in terms of geometry, strength, stiffness, and deformation characteristics of the ground model. This integrated approach allows selecting and designing the appropriate foundation solution, enhances prediction accuracy, reduces uncertainty, and ultimately contributes to the long-term stability, cost-effectiveness, and reduced risk profile of Wave and Tidal Energy systems. This paper summarises common site investigation techniques for WEC projects and presents some results of the integration of geophysical and geotechnical surveys for marine renewable energy projects.